Influence of Blastocysts Morphological Score on Pregnancy Outcomes in Frozen-thawed Blastocyst Transfers： a Retrospective Study of 741 Cycles - 刘琳 李艳辉 丁晓芳 耿育红 陈春艳 高颖 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
The influence of inner cell mass （ICM） and trophectoderm （TE） score on pregnancy out- comes in frozen-thawed blastocyst transfer cycles was analyzed. A retrospective analysis of 741 cycles of frozen-thawed blastosysts transfer was performed. All cycles were divided into four groups based on the number and morphological score of blastocysts： S-ICM B/TE B group （n=91）, the single blastocyst transfer oflCM B and TE B; D-ICM B/TE B group （n=579）, double blastocysts transfer oflCM B/TE B; D-1CM B/TE C group （n=35）, double blastocysts transfer of ICM B/TE C; and D-ICM C/TE B group （n=36）, double blastocysts transfer ofTE B/ICM C. The pregnancy outcomes were compared among the four groups. As compared with D-ICM B/TE C group, the clinical pregnancy rate, implantation rate and multiple pregnancy rate were increased in D-ICM B/TE B group （74.96% vs. 57.14%, 57.43% vs. 37.14%, and .48.62% vs. 25%, respectively, P〈0.05 for all）. Clinical pregnancy rate and implantation rate in D-ICM B/TE B group were also higher than in D-ICM C/TE B group （74.96% vs. 50%, and 57.43% vs. 33.33%, both P〈0.05）. Multivariable Logistic regression analysis indicated that ICM score was a better predictive parameter for clinical pregnancy （OR=3.05, CI 1.70-5.46, P〈0.001）, while the trophectoderm score was a better one for early abortion （OR=0.074, CI 0.03-0.19, P〈0.001）. Clinical pregnancy rate and multiple pregnancy rate in S-ICM B/TE B group were significantly lower than those in D-ICM B/TE B group （46.15% vs. 74.96%, and 2.38% vs. 48.62%, both P〈0.05）, but there was no si~,,niflcant difference in the implantation rate between the two groups. It was suggested that the higher score of ICM and TE may be indicative of the better pregnancy outcomes. The ICM score is a better predictor of clinical pregnancy than TE, while TE score is a better one in predicting early abortion. Sin- gle ICM B/TE B blastocyst transfer in frozen-thawed cycles can also get satisfactory pregnancy out- comes.